Extraction Methods Development and Optimization for Chromatographic Analysis of Pharmaceuticals in Sediment - Ašperger, D.; Cerić, D. (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2018)
Pharmaceuticals are so-called emerging contaminants whose occurrence in the environment is still not law regulated. In this work, pharmaceuticals belonging to different structure groups were determined in sediment samples and five extractions were developed and optimized: EA, USE, MAE, MSPD and PSE. Chosen pharmaceuticals were tylosine (macrolide antibiotic), albendazole, febantel and levamisole (antihelmintics), lidocaine and procaine (anaesthetics), and hydrocortisone and dexamethasone (glucocorticoids). Pharmaceutical concentrations extracted from sediment were determined by HPLC using a diode array detector. All methods were validated and optimal parameters were determined for each extraction method, including sediment mass, solvent, contact time, extraction duration, agitation frequency, and extraction temperature.